2012
DOI: 10.1109/tsp.2011.2168522
|View full text |Cite
|
Sign up to set email alerts
|

Non-Systematic Complex Number RS Coded OFDM by Unique Word Prefix

Abstract: Abstract-In this paper we expand our recently introduced concept of UW-OFDM (unique word orthogonal frequency division multiplexing). In UW-OFDM the cyclic prefixes (CPs) are replaced by deterministic sequences, the so-called unique words (UWs). The UWs are generated by appropriately loading a set of redundant subcarriers. By that a systematic complex number Reed Solomon (RS) code construction is introduced in a quite natural way, because an RS code may be defined as the set of vectors, for which a block of su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 24 publications
2
74
0
Order By: Relevance
“…In UW-OFDM, this guard interval is part of the DFT interval, i.e., the last N u samples of the DFT interval are reserved for the unique word, which is a sequence of known samples. In [1], it is shown that UW-OFDM outperforms cyclic prefix (CP-) OFDM with respect to the bit error rate in fading channels. This is confirmed in [2] where a theoretical analysis of the error rate performance shows that UW-OFDM is always able to achieve full diversity, whereas in CP-OFDM only a diversity one is obtained unless precoding is used.…”
Section: Uw-ofdmmentioning
confidence: 99%
“…In UW-OFDM, this guard interval is part of the DFT interval, i.e., the last N u samples of the DFT interval are reserved for the unique word, which is a sequence of known samples. In [1], it is shown that UW-OFDM outperforms cyclic prefix (CP-) OFDM with respect to the bit error rate in fading channels. This is confirmed in [2] where a theoretical analysis of the error rate performance shows that UW-OFDM is always able to achieve full diversity, whereas in CP-OFDM only a diversity one is obtained unless precoding is used.…”
Section: Uw-ofdmmentioning
confidence: 99%
“…The redundant carrier symbols and the energy assigned to them depend on the choice of P through M. By using (4) in (1), it can be seen that the redundant carriers introduce correlations in the frequency domain data vector x. Different redundant carrier placement approaches are introduced such that the energy spent on redundant carriers is minimized [15], [16].…”
Section: −1mentioning
confidence: 99%
“…In a two-step implementation of UW-OFDM systems, first a block of zeros is constructed at the tail of the IDFT output. This can be done by two approaches [4]: 1) by appropriately loading a set of redundant carriers in systematic coded UW-OFDM system, i.e. data carriers and redundant carriers are separated, and 2) by distributing the redundancy over all active subcarriers by using a code generator matrix in non systematic coded UW-OFDM system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations